Development and characterization of a babassu nut oil-based moisturizing cosmetic emulsion with a high sun protection factor. Issue 44 (13th July 2020) - Silva, Michael Jackson Ferreira da; Rodrigues, Alisson Mendes; Vieira, Italo Rennan Sousa; Neves, Gelmires de Araújo; Menezes, Romualdo Rodrigues; Gonçalves, Eloisa da Graça do Rosário; Pires, Maria Célia Costa
Abstract : A stable moisturizing cosmetic emulsion was developed from babassu nut oil and high concentrations of sunscreens. Abstract : A stable moisturizing cosmetic emulsion was developed from babassu nut oil and high concentrations of sunscreens. Babassu nut oil was chosen because within the laboratory time-scale, this vegetable oil showed stable physicochemical properties (relative density, acidity index, and refracted index) and a good ratio between lauric and myristic fatty acids. The presence of these saturated fatty acids can confer specific activities to the cosmetic emulsion, such as antiviral, bactericidal, and anti-inflammatory activity. The prepared cosmetic emulsion, even after the centrifugation test (3000 rpm for 15 min), showed a creamy appearance with stable light-yellow coloration and the typical odor of babassu nut oil-based products. In the accelerated stability assays (pH, viscosity, and globule homogeneity), the cosmetic emulsion was kept at different temperatures (2.0 ± 0.2 °C ( T G ), 25 ± 2 °C ( T A ), and 40 ± 2 °C ( T E )) and time durations (24 hours ( t 0 ), 7 days ( t 7 ), 15 days ( t 15 ), and 30 days ( t 30 )). Finally, developed the cosmetic emulsion was investigated for occlusive properties and in vitro sun protection factor (SPF). Both were measured at room temperature and did not change significantly under the experimental conditions employed. The maximum experimental value measured in the in vitro occlusive test was equal to 34.2 ± 2.8, and the SPF was 39 ± 1.6 ( t 0 ) and 38 ± 2.9 ( t 30 ). In agreement with European and Brazilian legislations, the obtained babassu oil-based cosmetic emulsion is classified to have a high sun protection factor.